Study Effectiveness of Management Information Systems and Organizational Culture on Productivity Work Accounting Department Employees - Sari, Nur Zeina Maya Sari; Nurdin, Rakhmat; Sondary, Tanty (Ilomata International Journal of Management, 2024)
To achieve the company's goals must have productivity employee good. Good work enthusiasm high and employee performance both will help the company achieve its goals. The development of management information systems has led to changes in the role of managers in decision making, they are required to always be able to obtain the most accurate and up to date information that they can use in the decision-making process. In making a decision. in management information systems decision making initial company management often​​​​ by​ there are many factors​​​​ n on t e now s be accurate, relevant, complete and timely . Organizational culture has a very strategic role in encouraging and improving organizational performance, both long and short term. The use of Management Information Systems in automating company operations can help companies save time and reduce costs, and also increase employee productivity. This research was conducted by distributing questionnaires to employees with a sample of 33 respondents. This research was processed statistically using SEM-PLS. It is hoped that the results of this research will be solution in finish problem productivity Work employee in the Accounting Department. . This research shows that: 1 ) The effectiveness of the Management Information System influences employee work productivity. 2 ) Organizational culture influences employee work productivity department accountancy .